Hypersensitivity to polyethylene glycol in adults and children: An emerging challenge: Hypersensitivity to polyethylene glycol - Bianchi, Annamaria; Bottau, Paolo; Calamelli, Elisabetta; Caimmi, Silvia; Crisafulli, Giuseppe; Franceschini, Fabrizio; Liotti, Lucia; Mori, Francesca; Paglialunga, Claudia; Saretta, Francesca; Tosca, Mariangela; Cardinale, Fabio; et al. (Acta Biomedica Atenei Parmensis, 2021)
Hypersensitivity reactions to polyethylene glycol (PEG) is an emerging challenge and the interest about this disease is growing since PEG is considered one of the possible causes of coronavirus disease 2019 (COVID 19) vaccine-associated anaphylaxis. PEG is used in a wide variety of pharmaceutical, medical, industrial, cosmetic, and food products and can be an active ingredient or used as an excipient. PEG is present in several medications, and it may or may not be present in different formulations and dosages of the same drug. Lack of standardization nomenclature, inadequate labelling of products and lack of knowledge about PEG involvement in hypersensitivity reactions expose patients at risk of presenting multiple reactions before a diagnosis could be made. In this review we describe the main cases published in literature and propose an allergy work-up and management.